2020
DOI: 10.1111/apt.15708
|View full text |Cite
|
Sign up to set email alerts
|

Letter: suicide risk among adult inflammatory bowel disease patients

Abstract: LINKED CONTENT This article is linked to Malham et al papers. To view these articles, visit https://doi.org/10.1111/apt.15258 and https://doi.org/10.1111/apt.15733.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Various researchers studied the risk factors of depression among patients with IBD and concluded that age, severe disease, flare ups, disability, unemployment, socioeconomic impairment [104] and coronavirus disease 2019 isolation due to extensive lockdown measures are factors responsible for developing depressive symptoms [105]. Various studies highlight the increased risk of suicide among IBD patients [106][107][108].…”
Section: Mentalmentioning
confidence: 99%
“…Various researchers studied the risk factors of depression among patients with IBD and concluded that age, severe disease, flare ups, disability, unemployment, socioeconomic impairment [104] and coronavirus disease 2019 isolation due to extensive lockdown measures are factors responsible for developing depressive symptoms [105]. Various studies highlight the increased risk of suicide among IBD patients [106][107][108].…”
Section: Mentalmentioning
confidence: 99%